2018
DOI: 10.1055/s-0038-1667185
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Preterm Delivery using the Fetal Fibronectin Test Associated with the Measurement of Uterine Cervix Length in Symptomatic Pregnant Women

Abstract: In symptomatic pregnant women, we concluded that the MUCL < 25 mm associated with positive fFN rapid test indicate increased the risk for PTD. Further studies with larger sample sizes could contribute in supporting the results presented in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have confirmed that a cervical length <25 mm on ultrasound examination in the second trimester is a powerful predictor of preterm delivery in patients with a history of PTB or STL or without a history of PTB and STL [3,4,16,17] . Based on a review of the literature, very few studies have systematically investigated the indications for conservative treatment or cervical cerclage among patients with a sonographic short cervix (<25 mm) [9,18–23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that a cervical length <25 mm on ultrasound examination in the second trimester is a powerful predictor of preterm delivery in patients with a history of PTB or STL or without a history of PTB and STL [3,4,16,17] . Based on a review of the literature, very few studies have systematically investigated the indications for conservative treatment or cervical cerclage among patients with a sonographic short cervix (<25 mm) [9,18–23] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that a cervical length <25 mm on ultrasound examination in the second trimester is a powerful predictor of preterm delivery in patients with a history of PTB or STL or without a history of PTB and STL. [3,4,16,17] Based on a review of the literature, very few studies have systematically investigated the indications for conservative treatment or cervical cerclage among patients with a sonographic short cervix (<25 mm). [9,[18][19][20][21][22][23] In the To et al [18] study, 253 women with a short cervical length ( 15 mm) were measured by transvaginal ultrasound between the 22 and 24 weeks gestation agreed to participate in a randomized study of cervical cerclage.…”
Section: Discussionmentioning
confidence: 99%